Sternal swelling presenting as tuberculosis: a case report - John Rajan; Khaled Bizanti (Journal of Medical Case Reports, 2021)
Abstract Background Tuberculosis continues to be a worldwide public health problem. Despite the noted gradual decline in tuberculosis case rates in the UK, clinicians should still be aware of these unusual presentations. Sternal tuberculosis is an uncommon form of extrapulmonary tuberculosis and it can initially be a diagnostic challenge for paediatricians. These lesions can present with nonspecific signs and symptoms that may mimic malignancy. Case presentation We present a case of a 3-year-old African descent girl with a sternal swelling that was confirmed to be Mycobacterium tuberculosis complex DNA on gastric aspirate. The child had additional radiological investigations that corresponded accordingly. She was started on quadruple antituberculosis therapy with good outcome. Conclusion Tuberculosis sternal abscess is as rare finding, especially in developed countries where tuberculosis is not endemic. Tuberculosis may not always present with pulmonary symptoms in children. There should be a high suspicion of tuberculosis, especially in immigrant population presenting with unusual presentations. Our aim is to increase awareness around atypical presentations of tuberculosis in children. Although, tuberculosis is endemic to underdeveloped countries, clinicians should still be aware of presentations in view of current global migration.